Macromol. React. Eng. 12/2013. Issue 12 (December 2013) - Zeng, Yanning; Matta, Akanksha; Dwivedi, Sumant; Taniike, Toshiaki; Terano, Minoru
<x xml:space="preserve">Abstract</x> Cover: Transition metals, introduced as the second component in bimetallic Phillips catalysts, enhance their ethylene polymerization activity. In particular, second metals with low electronegativity decrease the electron density on the chromium species and therefore, improve the branching ability in ethylene polymerization. Further details can be found in the article by Y. Zeng, A. Matta, S. Dwivedi, T. Taniike, M. Terano* on page 668. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>